Pelaksanaan Eksekusi Hak Tanggungan oleh Kreditur yang Dilakukan Sebelum Jatuh Tempo Perjanjian: Studi Putusan Yurisprudensi PutusanMahkamah Agung Nomor 3/Yur/Ag/2018 - Sarah Nabila; Ruslan Ruslan; Adi Mansar Lubis (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The execution of Mortgage Rights (Hak Tanggungan) represents legal certainty as regulated in Law Number 4 of 1996 concerning Mortgage Rights. Execution of the collateral object can be carried out through private sale, parate execution, or based on an executorial title. This mechanism reflects good faith and trust between the creditor and debtor in a lending agreement. In line with Sharia principles, the murabahah financing contract also allows for collateral (rahn tasjily), granting the creditor the authority to execute the collateral object if the debtor defaults. This study aims to analyze the implementation of Mortgage Rights execution in Sharia financing, specifically under the murabahah contract. The method used is normative juridical research with a descriptive approach, employing statutory and case study analysis, and based on literature and relevant regulations. The results indicate that land rights can serve as collateral under Mortgage Rights in Sharia financing. This is confirmed in the Supreme Court Decision Number 179K/Pdt/2017, which serves as jurisprudential precedent for Decision Number 3/Yur/2018, where the collateral is executed through a Deed of Granting Mortgage Rights. The position of the creditor in a murabahah contract is equivalent to that in conventional financing, as confirmed in the DSN-MUI Fatwa, thus the creditor retains the right to execute even if the debtor defaults before the due date.